Consumer Perceptions of Organic Products: A Study in Birendranagar, Surkhet (The International Research Journal of Management Science, 2023)
Purpose: The purpose of this study is to examine how consumers in Birendranagar, Surkhet, Nepal, perceive organic products. It aims to uncover variables influencing customers' purchasing decisions in the area and offer insightful information on the market demand for organic products.Method/ Design: A convenience sampling method was used to gather the data where 200 respondents were given a survey questionnaire in the study region. The goal of the survey was to learn about the attitudes, convictions, and perceptions of consumers regarding organic products.Findings: The findings show that various key factors remarkably impact consumer perception towards organic products. These factors include awareness and knowledge of organic products, perceived benefits of organic products, price sensitivity, trust in organic labeling and certification, and the availability of organic products in the market.Practical Implications: The findings of this study provide useful and practical insights for businesses operating in the organic products market. Increasing consumer awareness about the health and environmental benefits of organic products and ensuring the availability of such products in the market can play an important role in expanding organic products market. Businesses can use this information to tailor their marketing strategies and product offerings to better meet consumer preferences.Originality/Limitation of the Study: This study contributes to the growing body of research on consumer perception of organic products, particularly in the context of Birendranagar Surkhet, Nepal. It's crucial to remember that this study's conclusions are unique to this area and might not apply to other places. An expanded comprehension of consumer behavior about organic products can be obtained through additional study conducted in various geographic regions.